O modelo de barras como recurso na resolução de problemas algébricos - Fontes, Gabriel de Oliveira (2019)
According to Saeb data (assessment used by the federal government to measure student learning at the end of each stage), most Brazilian students do not achieve results considered sufficient when referring to mathematics teaching, considering that it is sufficient to perform operation with natural numbers or recognizing function graphs, who knows that these students have a minimal understanding of algebra. Therefore, the work foresees the study of a model for teaching algebra that became known in Singapore, which obtained excellent results in international exams. In addition, the work has the resolution of 7 problems, using the Singapore model together with the Problem Solving which aims at four steps that were proposed by Polya, they are: Understanding the Problem, Establishing a Plan, Implementing the Plan and Retrospect. These two methodologies aim to serve as a basis for mathematics teachers in algebra teaching. The paper also presents a brief understanding of the transition process from arithmetic to algebra, recognizing that understanding this process facilitates the teacher to find the difficulties of students. During the resolution of each problem, we tried to create, in some points, dialogues between teacher and student, trying to simulate the teaching-learning environment, besides providing what started the work, improving the training of mathematics teachers.